THE CONCEPT AND IMPLEMENTATION OF SUBSTITUTE HEIRS AT THE SHARIA COURT OF ACEH PROVINCE, INDONESIA - Yunus, Ilyas; Rani, Faisal A.; Mahfud, Mahfud; Muzakkir, Muzakkir (Universitas Syiah Kuala, 2024)
The Quran and Hadiths specify rightful recipients of Zawil Furudl inheritance, creating a loophole for substitute heirs. Islamic scholars debate the concept of successor inheritance. This study explores substitute heirs and their status as alternate beneficiaries in Aceh's Sharia Court. The Aceh community rejects substitute heirs due to classical philosophy requiring the successor to be alive at the original heir's death. Despite not being present in fiqh and adat literature, substitute heirs are recognized in the Shariah Court under Article 185 of the Indonesian Compilation of Islamic Law. This recognition aligns with the objectives of Islamic law for justice and benefit. Legal pluralism allows for this practice, emphasizing harmonization between legal systems